Keutamaan Santo Yusuf sebagai Teladan Hidup Katekis dalam Karya Pastoral - Mario Helarius Purba; Kristiana Mendrofa; Blasius Superma Yese (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This thesis departs from the author's awareness and interest in getting to know the lives of Christian believers who are struggling to practice their faith in this world. This thesis describes that Saint Joseph was a saint whose name was familiar to the ears of the faithful. Saint Joseph was god's choice to be entrusted to be the father of the Son of God, Jesus Christ. Saint Joseph performed these duties and responsibilities humbly and faithfully to the Lord's commands. The Church then reflected on the life of this Saint Joseph and made him the Protector of the Universal Church, the Protector of the Holy Family of Nazareth, and the Protector of the Workers' Fig. Just as Saint Joseph made his life a servant of God's plan, so too did the faithful realize his calling as a herald of love. The faithful are invited to always see what God wants in a crisis-stricken life, while still trying to find creative ways and efforts to solve all of life's problems. Thus, this example of the primacy of Saint Joseph can lead the faithful to remain faithful to God until they are finally able to achieve eternal unity with God in heavenly happiness.